Implementasi Kebijakan Disiplin Aparatur Sipil Negara Pada Sekretariat Dewan Perwakilan Daerah Kabupaten Mamuju - Muhammad Akbar S; Yenni Yenni (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
This research aims to determine the implementation of state civil servant discipline policies at the secretariat of the regional people's representative council of Mamuju district. This type of research is qualitative research and the type of research uses a descriptive approach. The population in this study were all civil servants at the Secretariat of the Mamuju Regency Regional People's Representative Council. Based on the research results, it can be concluded that "Implementation of Discipline Policy for State Civil Servants at the Secretariat of the Regional People's Representative Council in Mamuju Regency" in this case Law Number 94 of 2021 Amendment to Law Number 15 of 2014, PP Number 94 of 2021 concerning State Civil Servants, this Law was created to regulate the rules regarding work discipline for Civil Servants. This law also regulates that State Apparatus must not be biased towards the political axis or need to have a neutral attitude towards politics.